2019
DOI: 10.1177/0047239518821937
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Social Network Messaging App on Team Cohesiveness and Quality of Completed Team Projects in an Undergraduate Team Project

Abstract: This research sought to determine what impact a social network messaging app could have on student’s team project performance. The app allowed students to self-select teams based on user profiles within the app. The study investigated three hypotheses that measured the apps impact on the quality of completed team projects, the team’s sense of shared goals, and team cohesiveness. The findings suggested that social network messaging apps that provide a sense of common ground between team members may better engag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…When members encounter external competition or a difficult goal, team cohesiveness tends to strengthen (Holmgrenn et al, 2017). Matt Graham and Jones (2019) have suggested that carrying out multiple tasks at the same time may produce positive results and may also lead to negative results, and it is critical to identify the time conditions during which they act.…”
Section: The Moderating Role Of Team Cohesivenessmentioning
confidence: 99%
See 2 more Smart Citations
“…When members encounter external competition or a difficult goal, team cohesiveness tends to strengthen (Holmgrenn et al, 2017). Matt Graham and Jones (2019) have suggested that carrying out multiple tasks at the same time may produce positive results and may also lead to negative results, and it is critical to identify the time conditions during which they act.…”
Section: The Moderating Role Of Team Cohesivenessmentioning
confidence: 99%
“…The cohesiveness of a team refers to how individuals are drawn to and motivated to stay on the team (Wendt et al, 2009). Team cohesiveness occurs when team members believe their team will assist them in achieving their need for affiliation or status and achieving a common goal (Shin and Park, 2009;Matt Graham and Jones, 2019). As a result, sociologists have classified team cohesiveness into two categories: socioemotional cohesiveness and instrumental cohesiveness (Bozanta et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mobile communication is now a part of everyday life for most people. In 2021, the global number of mobile messaging users is estimated to grow to 2.48 billion (Graham, & Jones, 2019). Mobile instant messaging applications (MIMAs) differ from traditional telecom communication patterns, enabling communication regardless of the network platform or mobile device.…”
Section: Introductionmentioning
confidence: 99%